Some Cryptographic Weakness and the Ways to Avoid Them in ICT Services of Developing Countries. - Hyka, Dolantina; Benusi, Ardi (European Journal of Sustainable Development, 2014)
One of the best ways to learn cryptography is to exercise their skills on encrypting and decrypting algorithms through different examples on corresponding cryptosystems (RSA [5], Massey-Omura [8], EMO1 [6], EMO2 [6],etc). Everyone have to try solving them by doing computations. Sometimes even following a wrong method one may get the right answer. Following the idea presented in [1], [2], [3], we have presented here a maple algorithm to generate strong or diagnostic[7] cryptographic examples over Finite Field and Elliptic Curves. The Maple algorithm presented, generate diagnostic exercises, in which all error paths lead to different answers. Using it one can easily generate exercises that are sound so a student who makes errors in algorithm steps computing will get the wrong answer. This conclusion can also be used even in constructing algorithms not only in cryptography but also in other disciplines for example generating matrix different types matrix equations and being sure about the number of solutions without solving them first, or generating economic examples ect… Keywords: ICT, strong example, sound example, diagnostic example, EMO1, EMO2, Fiat – Shamir, ect...